Genetic diversity of chemokine XCL1 and its receptor XCR1 in murine rodents. (September 2019) - Xu, Feifei; He, Dan; Ning, Ruihong; Zeng, Bo; Thompson, Cody W.; Li, Ying; Wang, Dawei; Li, Yan
Abstract: The chemokine ligand XCL1 plays critical roles in immune responses with diverse physiological and pathological implications through interactions with a cognate G protein-coupled receptor XCR1. To shed insight into their versatile nature, we analyzed genetic variations of XCL1 and XCR1 in murine rodents, including commonly-used model organisms Mus musculus (house mouse) and Rattus norvegicus (Norway rat). Our results showed that adaptive selection has contributed to the genetic diversification of these proteins in murine lineage. Moreover, in both M. musculus and R. norvegicus, the chemokine and its receptor exhibit similar signs of selective sweeps resulting from positive selection. In light of currently available structural and interaction information for chemokines and their receptors, the similarity of XCL1/XCR1 evolutionary patterns among murine species and the parallels of their evolutionary footprints within individual species suggest that interplay could exist between the adaptively selected changes, or between the domains on which the identified changes are located, and consequently preserve the physiological interaction of XCL1 and XCR1. Highlights: Chemokine XCL1 and its receptor XCR1 experienced adaptive diversities in the rodent subfamily Murinae. Adaptive changes occurred on a number of amino acid sites of XCL1 and XCR1. In both Mus musculus and Rattus norvegicus, XCL1 and XCR1 exhibit similar signs of selective sweeps.